Saringkararot in Phra Abhai Mani - อำพันธ์, จุรีย์พร; พลมณี, ศรีวิไล; สัตโยภาส, สนิท (Ganesha Journal, 2018)
The objective of the research was to examine Saringkararot in Phra Abhai Mani by studying 64 parts of Phra Abhai Mani, Thai tradition literature written by Sunthorn Phu. According to theory of Saringkararot, love was divided as 2 types; one Samphokha and Wipralampha. 1. Samphokha: love of the person who lived together with his beloved person; for example, love between Srisuwan and Ketsara, love between Phra Abhai Mani and Suwanmalee, love between Phra Abhai Manni and Laweng, love between Sinsamut and Arunrasmi, love between Sudsakorn and Saowakon, love between Hassachai and Soisuwan and Chantasuda, love between King Sutad and Patoom Kesorn, love between King Tossawong and his wife, love between King Suriyothai and Chantarawadee, love between Brahman Wichien and Prapawadee and love between Brahman Sanon and Ubonrassamee. 2. Wipralampha: love of the person who was far away or separated from his beloved person; for example, love between Phra Abhai Mani and Nang Phisue Samut, love between Phra Abhai Mani and the mermaid, love between Phra Abhai Mani and Nang Walee, love between Srisuwan and Nang Ramphasari, love between Sinsamut and Nang Yuphapaka and love between Sudsakorn and Nang Sulaleewan. It was found that Saringkararot appeared in 64 parts in this Thai tradition literature, Phra Abhai Mani, had the form of love which was summarized as love towards person divided as love towards heirs, love towards parents, love towards relatives and love towards opposite gender.